THE EFFECT OF CUSTOMER EXPERIENCE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION TO USERS OF TRANSPORTATION SERVICES ONLINE IN MEDAN CITY - Ira Hairani Br. Damanik; Fadli; Syafrizal Helmi Situmorang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to determine and analyze the effect of customer experience on customer loyalty with customer satisfaction as an intervening variable for users of online transportation services in Medan City. The population in this study is the people in Medan City, especially Medan Amplas District who have used Grab, Gojek and Maxim. The sampling technique in this study was non-probability sampling of 180 respondents. The data analysis method uses Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that Customer Experience had a positive and significant effect on Customer Loyalty, Customer Experience had a positive and significant effect on Customer Satisfaction, Customer Satisfaction had a positive and significant effect on Customer Loyalty,